Improvement of Grapevine Iron Nutrition by a Bovine Blood-Derived Compound - Tessarin, P.; Ingrosso, E.; Rombola, A. D.; Boliani, A. C. [UNESP]; Covarrubias, J. I.; Yunta, F.; Poovarodom, S.; Yingjajaval, S. (Int Soc Horticultural Science, 2013)
Iron (Fe) is essential for chlorophyll formation and plant growth. Iron-deficiency chlorosis is a major nutritional disorder in several fruit trees cultivated in calcareous and alkaline soils, reducing fruit yield and quality and causing heavy economic losses. Since chelated Fe, the most widespread fertilizers used for preventing or curing Fe deficiency, pose risks of environmental pollution, the development of sustainable agronomic alternatives represents a priority for the fruit industry. In this work, we investigated the effectiveness of a bovine blood-derived product (BB; 0,125% Fe) for preventing Fe-deficiency in grapevine plants. During the vegetative season 2011 potted plants of five graft combinations: Sangiovese/SO4, Cabernet Sauvignon/SO4 and Cabernet Sauvignon/140 Ruggeri, 140 Ruggeri/Cabernet Sauvignon, Vitis riparia/Cabernet Sauvignon were grown on calcareous soil. Soil treatments included: 1) Control; 2) Fe-EDDHA (Fe 6%); 3) Bovine-Blood (5 g/L); 4) Bovine-Blood (20 g/L). With the exception of Cabernet Sauvignon/SO4 plants, Fe-EDDHA increased SPAD units (leaf chlorophyll content). Bovine-blood at low concentrations had similar or higher SPAD units than Fe-EDDHA. Increasing concentration resulted in further increases in SPAD units only in some graft combinations. Data highlight the efficiency of Fe blood-compound in the prevention of grapevine Fe-deficiency over one growing season.
Keywords: Fe-deficiency; Fe chlorosis; sustainability; viticulture; graft combinations